ChemInform Abstract: Enhancing the Reversibility of Mg/S Battery Chemistry Through Li+ Mediation. Issue 2 (23rd December 2015) - Noked, Malachi; et al.,
Abstract: (CF3 SO2 )2 NLi is added to the non‐nucleophilic ((Tms)2 N)2 Mg electrolyte used in a Mg/S secondary battery system with an activated carbon/sulfur cathode and Mg foil as anode separated by a Whatman glass fiber separator.